DESIGN AND ANALYSIS OF SOIL IMPROVEMENT USING CONTROLLED MODULUS COLUMN CASE STUDY: APRON TERMINAL 3 OF SOEKARNO HATTA AIRPORT, CENGKARENG, TANGERANG - Diniastri Irmaputri, Khalista
Project of apron widening in Terminal 3 of Soekarno Hatta Airport, Cengkareng, Tangerang, which is the case study of this theses, is predicted to meet problem in bearing capacity and settlement of the soil deposit. To overcome this problem, soil improvement using Controlled Modulus Column is to be used. Controlled Modulus Column is a soil improvement method by replacing the soil with gravel material that has better shear strength parameter than the original soil. In general, Controlled Modulus Column is similar to stone column in the design aspect. The difference between the two are in construction method and quality control during construction. The design of Controlled Modulus Column is performed by using method from Priebe’s journal, titled “The Design of Vibro Replacement” (1995). Configuration of CMC used in this theses is rectangular. Diameter of CMC is 0,8 meter, spacing between CMCs is 2 meter. The length of CMC is 7,6 meter, and between the CMCs and the soil surface, a load transfer platform is installed. This 0,4 meter thick platform is used for transferring load from the surface to CMCs and soil deposit beneath. Calculation method used in this theses is by using Plaxis and DC-Vibro software. Plaxis software will analyze settlement occured in models and reached safety factor. DC-Vibro software has the same principal as Priebe, therefore the output produced by the software are improvement factor, occured settlement, and safety factor. Soil improvement using CMC is to reduce settlement occured in soil deposit, to accelerate consolidation process, and to increase bearing capacity of improved soil.